2000
DOI: 10.1111/j.1528-1157.2000.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Kindling of the Bilateral Hippocampi: An Advanced Model for Epilepsy Research

Abstract: Kindling has been recognized as an animal model of human epilepsy. The standard kindling paradigm, first described by Goddard et al. (1,2), involves the repeated delivery of an electrical current through an implanted electrodc to a single forebrain site in mammals (3-6) of sufficient intensity to evoke an afterdischarge (AD). Recently, a modification of the standard kindling model known as alternate-site kindling has been reported (7-13). 11 involves the concurrent, alternate stimulation of two forebrain struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Since its first descriptions over 20 years ago this phenomenon has been examined for the potential underlying mechanisms as the observation is almost counterintuitive, that seizures from one site would suppress seizures from another. Some factors have become clear: norepinephrine can play a role in modulating antagonism, that antagonism is protocol and site specific and that it may not occur in all species (Applegate et al, 1986; Teskey et al, 1999; Kogure et al, 2000; Matsuda et al, 2003). Does the observation have relevance for human epilepsy?…”
Section: Kindling To Spontaneous Seizuresmentioning
confidence: 99%
“…Since its first descriptions over 20 years ago this phenomenon has been examined for the potential underlying mechanisms as the observation is almost counterintuitive, that seizures from one site would suppress seizures from another. Some factors have become clear: norepinephrine can play a role in modulating antagonism, that antagonism is protocol and site specific and that it may not occur in all species (Applegate et al, 1986; Teskey et al, 1999; Kogure et al, 2000; Matsuda et al, 2003). Does the observation have relevance for human epilepsy?…”
Section: Kindling To Spontaneous Seizuresmentioning
confidence: 99%
“…The R-A was used for stimulating as well as injecting. The stimulus train for PADs was 1-ms pulses of 50 Hz for 1 s (30,31,34,35). In preliminary experiments, electrical stimuli <100 A could hardly produce paroxysmal discharges.…”
Section: Stimulation and Injectionmentioning
confidence: 99%
“…We have previously reported that the hippocampal interneuron showed a long-lasting burst discharge before the initiation of spontaneous seizure discharge in the short-term experiment using kindled rabbits, and that the apical dendrites of pyramidal cells exhibited an abnormal active property during kindling (30)(31)(32). Taking our data and several characteristics of Ih channels into consideration, we hypothesized that an anomalous hyperpolarization generates an abnormal excitation by way of Ih channels.…”
mentioning
confidence: 99%
“…Kindling is a canonical model used for the study of epileptogenesis, yet it receives increasing criticism due to the lack of SRS. However, over-electrical kindling ultimately results in SRS ( Kogure et al, 2000 ; McIntyre et al, 2002 ). Recent research revealed eight day consecutive flurothyl-kindling is sufficient to elicit SRS immediately after kindling, which remits weeks later ( Kadiyala et al, 2016 ).…”
Section: Srs In Rodent Models Of Epilepsymentioning
confidence: 99%